An Evaluation on Ibrahim Madkur’s Critical Text Edition of Ibn Sina’s Ash-Shifa’ - Ahmad Fathan Aniq (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
Ibn Sīnā is one of the prominent scholars in the Muslim scientific world. In the West, he is well known as Avicenna. As a polymath, he wrote many books in a broad range of sciences. Al-Qānūn fī aṭ-Tibb (the Canon of Medicine) and Kitāb Ash-Shifā’ (the Boook of Healing) are considered to be his magnum opuses. While the former is his greatest work on medicine, the latter is his monumental contribution to science and philosophy. Kitāb Ash-Shifā’ is concerned with four main subjects: logic (al-manṭiq), natural sciences (aṭ-ṭabi’iyāt), mathematics (ar-Riyaḍiyāt), and metaphysics or theology (al-Ilāhiyāt).